Implementasi Kebijakan Pelaksanaan Program Uji Emisi Kendaraaan Bermotor dalam Rangka Mengurangi Polusi Udara di Wilayah Jakarta Timur - Ramdhani Riyanto; Hendra Wijayanto; Angella Rosha Pangestu; Sisman Prasetyo (Indonesian Journal Publisher, 2024)
Policies for carrying out the motorized vehicle emissions testing program are the focus of this research. Motorized vehicle emissions contribute to air pollution, which in turn affects environmental pollution and people's health, and this problem is getting worse as the number of vehicles on the road continues to rise. The main issue with this study is that, despite the policy of the motor vehicle emissions test program being in place, many drivers still choose not to follow it. This study combined a descriptive approach with a qualitative methodology. Methods such as observation, interview, and documentation were employed for the purpose of data collecting. The idea put forth by C. Edward III is utilized in this study; it comprises four distinct variables: (1) communication; (2) resources; (3) disposition; and (4) bureaucratic organization. Based on the findings, the Environmental Service's emissions testing program was doing a good job overall, although there was room for improvement in terms of public outreach